Hubungan antara Pembekalan Kewirausahaan dalam Pengelolaan Unit Bisnis Pondok Pesantren dengan Minat Berwirausaha Santri: (Studi Empiris Pada Santri di Pondok Pesantren Sabilul Huda Kota Tasikmalaya) - Wilva Ramadayanti; Andena Nur Hikmatunnisa; D Yadi Heryadi (Mikroba : Jurnal Ilmu Tanaman, Sains Dan Teknologi Pertanian, 2024)
The low interest of the community in entrepreneurship, which is often caused by the lack of early entrepreneurship education, is a major challenge. Islamic boarding schools, as religious-based educational institutions, have great potential to contribute to producing entrepreneurs through providing entrepreneurship to their students. This study analyzes the relationship between entrepreneurship provision in managing business units and the interest in entrepreneurship of students at the Sabilul Huda Islamic Boarding School, Tasikmalaya City, using a quantitative survey method. The sample consisted of 30 students who were actively involved in the Islamic boarding school business unit, with data collected through a Likert scale questionnaire. The results of the study showed that entrepreneurship provision had a positive and significant relationship with the interest in entrepreneurship of students, as evidenced by the correlation coefficient value of 0.653. This finding indicates that the better the entrepreneurship provision, the higher the interest of students in entrepreneurship. This study emphasizes the importance of the intensity and quality of entrepreneurship programs in supporting the development of competitive young entrepreneurs, especially in Islamic boarding schools, in order to support national economic growth.